Half-BPS vertex operators of the AdS5 × S5 superstring - Berkovits, Nathan [UNESP] (Springer Nature, 2019)
Using the pure spinor formalism for the superstring in an AdS5 × S5 background, a simple expression is found for half-BPS vertex operators. At large radius, these vertex operators reduce to the usual supergravity vertex operators in a flat background. And at small radius, there is a natural conjecture for generalizing these vertex operators to non-BPS states.
Keywords: AdS-CFT Correspondence; BRST Quantization; String Field Theory